Advances in iron deficiency and iron-related arrhythmias and cardiovascular diseases - Im, Sung Il (Frontiers in Cardiovascular Medicine, 2025)
Iron deficiency (ID) is common in patients with cardiovascular disease. Up to 60% of patients with coronary artery disease and even higher percentages of patients with heart failure (HF) or pulmonary hypertension have ID. However, the evidence for an association between ID including anemia and arrhythmias, particularly atrial fibrillation (AF) is less clear. The prevalence of ID increases with the severity of cardiac and renal dysfunction and would be more common in women. Increased blood loss due to antithrombotic therapy or gastrointestinal or renal disease and insufficient dietary iron intake, reduced iron absorption secondary to low-grade inflammation associated with congestion or reduced gastric acidity may cause ID. Both anemia and ID are associated with poor clinical outcomes, each may confer risk factors independently. There is growing evidence that ID is an important therapeutic target in patients with HF with reduced ejection fraction (HFrEF), even in the absence of anemia. Intravenous ferric carboxymaltose improved symptoms, ID-related quality of life, and exercise capacity and reduced hospitalizations for worsening HF in patients with HFrEF even mildly reduced EF (<50%). ID is easy to treat and effective in patients with HFrEF. These patients should be investigated for possible ID. Malnutrition has also been linked to cardiovascular disease. Both selenium and iron deficiencies have been associated with worse clinical outcomes in patients with HF. And selenium deficiency was associated with new-onset AF in nonsmoking participants. Interventional studies investigating the effects of optimizing the micronutrient status in at-risk populations are needed to assess causality, especially in those with ID. These recommendations may be extended to those populations based on evidence from future clinical trials.